The Effect of Audiovisual Integration on Performance Accuracy and Learning in Motor Task - Hesam Ramezanzade; Behrouz Abdoli; Alireza Farsi; Mohammad Ali Sanjari (Vesnu Publications, 2015)
Introduction: Vision is not the only sense providing information to understand the pattern of movement. Hearing is another suitable channel to gather information about the pattern of movement. Hence, this study investigated the effect of audiovisual integration on performance precision and learning in basketball jump shot. Materials and Methods: 30 subjects were selected. The subjects were randomly divided three groups: visual, visual-auditory (single channel) and visual-auditory (two channels). Visual group watched patterns killed basketball player and other groups other groups in addition to watching pattern skilled basketball player, heard Elbow angular velocity (one channel groups) and Elbow and wrist angular velocity (two channel groups) as sonification. Per session practice was including 40 try; and subject participated in four sessions .The acquisition test was done at the end of each session and retention test was performed after 48 hours. Data was analyzed by SPSS version 22. One-way ANOVA and repeated measures ANOVA was used for data analysis. Results: Results showed Visual-auditory group (single channel) had significantly better performance compared to visual group (P = 0.001) and visual-auditory group (two channels) (P = 0.045) inacquisition test. In retention test there was significant difference between auditory groups and visual group in favor of the auditory groups (P = 0.002 and P = 0.001, respectively). Conclusion: The results are consistent with modality appropriateness hypothesis. This results argues that due to certain temporal adjustments in jump shot basketball task, modality that dominates the perception in the context of this task, is auditory when is presented with visual simultaneously, it provide beneficial results. In this study, positive effect visual-auditory integration on performance and learning was confirmed.